Approaches to the realization of reproductive function in women with systemic lupus erythematosus and antiphospholipid syndrome - Galina A. Vlasova; Svetlana G. Perminova; Nadezhda M. Kosheleva (IP Berlin A.V., 2021)
Aim. To assess the safety and efficacy of assisted reproductive technology (ART) programs in patients with systemic lupus erythematosus (SLE) with/without comorbid antiphospholipid syndrome (APLS). Materials and methods. The observational study included 26 patients with diagnosed SLE, of whom 7 women had comorbid APLS and disorders of reproductive function. The analysis of the causes of impaired fertility was based on history and comprehensive examination data, which, along with risk factors for possible complications, determined the choice of ART programs. Results. In 23 of 26 patients, infertility (primary: 14, secondary: 9) was diagnosed, and 3 patients were diagnosed with repeated miscarriage. The main etiological factors of infertility were tubal (n=6), male (n=8) and their combination (n=3); in 9 cases the etiology of infertility remained unclear. 10 patients with a history of lupus nephritis had a reduced ovarian reserve. In total, 23 infertile patients underwent 33 in vitro fertilization programs. 11 (33%) clinical pregnancies were registered, of which 7 ended in live birth. There were no cases of severe exacerbation of SLE and thrombotic complications. Conclusion. ART can be used in patients with SLE with / without APLS, if the underlying disease is compensated for and prevention for complications is used. The effectiveness of ART programs is comparable to that in the general population. Further research is needed to make a final judgment on the safety of various ART programs in SLE with/without APLS.